2003
DOI: 10.1152/jn.00418.2003
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Rules for Upper and Lower Arm Contributions to Grasp Orientation

Abstract: The purpose of the current study was to investigate the contribution of upper and lower arm torsion to grasp orientation during a reaching and grasping movement. In particular, we examined how the visuomotor system deals with the conflicting demands of coordinating upper and lower arm torsion and maintaining Donders' Law of the upper arm (a behavioral restriction of the axes of arm rotation to a two-dimensional “surface”). In experiment 1, subjects reached out and grasped a target block that was presented in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 41 publications
3
22
1
Order By: Relevance
“…Most importantly, the data show that the forearm orientation is a reliable operationalization of the grasp orientation. The contribution of the forearm rotation to the overall rotation in Experiment 1 exceeded previous accounts, which showed that wrist and fingers as well as the forearm contributed roughly equally when grasping or manipulating objects (Herbort and Butz 2010;Marotta et al 2003). Most likely, the higher forearm contribution results from the task, which requires-unlike in the previous experimentsthat the fingers support the grasped object.…”
Section: Biomechanics Of the Forearm And Hand Rotationcontrasting
confidence: 56%
See 1 more Smart Citation
“…Most importantly, the data show that the forearm orientation is a reliable operationalization of the grasp orientation. The contribution of the forearm rotation to the overall rotation in Experiment 1 exceeded previous accounts, which showed that wrist and fingers as well as the forearm contributed roughly equally when grasping or manipulating objects (Herbort and Butz 2010;Marotta et al 2003). Most likely, the higher forearm contribution results from the task, which requires-unlike in the previous experimentsthat the fingers support the grasped object.…”
Section: Biomechanics Of the Forearm And Hand Rotationcontrasting
confidence: 56%
“…Even though fixating the accelerometer to the forearm did not enable measuring the hand's orientation directly, we used this method because in this way, no sensors at the fingers hindered the participants' interactions with the dial. Moreover, previous studies have shown that the orientation of the forearm is highly correlated with the orientation of the hand and thus a suitable operationalization (Herbort and Butz 2010;Marotta et al 2003).…”
Section: Data Recording and Analysismentioning
confidence: 99%
“…These data complement a number of extant studies that have made important contributions to neuroscience by documenting the spatiotemporal patterns of hand movement in various workspace configurations. For example, studies have explored how the shoulder and elbow angles are coordinated in pointing and reach-to-grasp tasks (Soechting and Lacquaniti, 1981;Lacquaniti and Soechting, 1982;Marotta et al, 2003) and tasks requiring pronation and supination of the forearm towards and away from the body (Alazmani et al, 2009). In contrast, there have been only a few studies that have contributed towards our understanding of the motive forces and torques required to affect movement of the upper limb joints.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that humans tend to think about grabbing objects in a hand-centric coordinate system, which implies that reaching motion also optimizes the distance the hand travels through the environment. Considering this observation along with motion capture experiments on people performing reaching tasks [17], we see that the hand roughly follows a linear trajectory to the target object roughly optimizing distance traveled in the workspace. Instead of designing a robot arm with an anthropomorphic structure as the first priority, we motivate the importance of translational motion in pick-and place tasks and design a robot arm that prioritizes translation (Fig.…”
Section: Introductionmentioning
confidence: 76%
“…For example, object fetching task from floor in house is combination of retrieving motion in x-axial direction and lifting up motion in z-axial direction to a desired height. Based on the observation that a human arm roughly follows a linear trajectory [17], we design a prismatic mechanism in the the forearm and upper arm of the robot.…”
Section: A Target Specificationsmentioning
confidence: 99%